Well-Being and Physical Health: A Mediation Analysis - Kesavayuth, Dusanee; Shangkhum, Prompong; Zikos, Vasileios (My University, 2022)
This paper’s aim is to propose a mediation framework and test whether lifestyle choices and social capital are pathways through which baseline levels of well-being affect subsequent physical health among older adults. Using large-scale panel data for Australia, we find that past levels of well-being have strong direct effects on present physical health. We also show that more frequent socialization and more frequent participation in physical activity are two pathways through which higher levels of well-being lead to better physical health. These mediating effects vary across gender. Our findings highlight a protective role of subjective well-being in physical health. Interventions taking into account not only the direct but also the indirect effects of well-being are promising avenues for physical health maintenance in the older population.
Journal of Happiness Studies
Keywords: Health and wellbeing